The Representation of Liberal Feminism in the Picture Book Mary Wears What She Wants by Keith Negley - Malau, Theophanie Clarissa; Kusumayanti, Dina Dyah; Supiastutik, Supiastutik (Humanus, 2024)
This research aims to show that women can dominate the story as seen in Negley’s picture book (2019) Mary Wears What She Wants. The theory used in this research is the theory of representation by Stuart Hall (1997). Besides, Barthes’ semiotic  theory (1957, 1968) is utilized to reveal the meaning of verbal and visual data in Negley’s picture book. This research is qualitative in its nature in which the data are the verbal as well as the visual texts of the picture book under study.  The finding of this research shows that the picture book under scrutiny represents inequality of gender rather than equality which highlight the inequality of women and men in the Victorian society. Another finding reveals that liberal feminism is represented through the main character, Mary. Mary dares to take risks to choose and decide the best for women, as she thinks that women have the rights to do anything they want without hesitation and with no limitation. This research also reveals that Mary uses her power to voice and to make changes impacting to women in her time. Because of her strive and determination, to date women have the bravery and power to do anything they want.